Global and Local Collaboration in Islamic Education Literacy Research - Loso Judijanto; Muhammad Rusdi; Muhamad Ammar Muhtadi (West Science Social and Humanities Studies, 2025)
This study explores the dynamics of global and local collaboration in Islamic education literacy research through a bibliometric analysis of literature sourced exclusively from the Scopus database. The analysis identifies key themes, such as the integration of global pedagogical practices with local Islamic traditions, the role of technology—particularly artificial intelligence and media literacy—in enhancing learning outcomes, and the importance of addressing sociopolitical challenges such as cyberterrorism through education. The findings reveal the centrality of collaboration among scholars and institutions in advancing the field, with networks highlighting influential contributors and interdisciplinary connections. Additionally, the study emphasizes the need for quality assurance frameworks and culturally relevant approaches to ensure the effectiveness of innovations in Islamic education. The results provide valuable insights for educators, policymakers, and researchers, offering a roadmap for enhancing Islamic education's relevance, accessibility, and impact in the digital era.